Wybrane zagadnienia aszanckiego pojęcia bliskości i oddalenia Istoty Najwyższej - Wita, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2004)
The article presents an indigenous way of Ashanti perception and their expressions of remoteness and closeness of their Supreme Being – Onyame. Attributes of uniqueness, omniscience and omnipotence point to God’s transcendence. The Ashanti reveal these ideas by using three honorary names for calling Onyame: Onyankopon Kwame, Anansi Kokroko and Odomankoma. This confirms absolute transcendence of Onyame’s nature. At the same time these West African peoples acknowledge permanent and immanent presence of Supreme Being among their life matters. This knowledge comes from the functions which Onyame plays as creator, king and protector of the Ashanti. Direct worship to Supreme Being is an exceptional consequence of this. Attributes of transcendence and immanence are paradoxically complementary. That is why one ought to treat them both as corrective and complex values. Only in that way one can build an adequate idea of the Ashanti Supreme Being.